SrNb0.1Co0.7Fe0.2O3−δ Perovskite as a Next-Generation Electrocatalyst for Oxygen Evolution in Alkaline Solution - Zhu, Y.; Zhou, W.; Chen, Z.; Chen, Y.; Su, Chao; Tadé, Moses; Shao, Zongping (Wiley-VCH Verlag, 2015)
The perovskite SrNb0.1Co0.7Fe0.2O3−δ (SNCF) is a promising OER electrocatalyst for the oxygen evolution reaction (OER), with remarkable activity and stability in alkaline solutions. This catalyst exhibits a higher intrinsic OER activity, a smaller Tafel slope and better stability than the state-of-the-art precious-metal IrO2 catalyst and the well-known BSCF perovskite. The mass activity and stability are further improved by ball milling. Several factors including the optimized eg orbital filling, good ionic and charge transfer abilities, as well as high OH− adsorption and O2 desorption capabilities possibly contribute to the excellent OER activity.